Researching Resilience - Liebenberg, Linda; Ungar, Michael, 1963- (Book collections on Project MUSE., 2009)
Researching Resilience challenges this tendency to pathologize youth, and marks a profound shift in research methods from the study of disorder to the study of well-being.